Spider Assemblage in Askot Wildlife Sanctuary:A High Altitude Ecosystem - Bandyopadhyay, Uttaran; Quasin, Shazia; Uniyal, V. P. (Indian Forester, 2016)
Spiders have a great ecological importance (such as bio-pesticides, prey for predators) and thus need thorough study and conservation. This is a study to build up a primary database for the Askot Wildlife Sanctuary (AWLS) region, collected from various habitats to assess the diversity and distribution. A total numbers of 40 quadrats were selected and sampled using semi-quantitative collection techniques such as: vegetation beating, ground hand collection, aerial hand collection and litter sampling. Overall 21 families (total 497 individuals) of spiders were recorded from AWLS area. Family composition varied substantially across the habitats with Oxyopidae (36.02%) being the most dominant group found followed by Lycosidae (22.33%) and then Salticidae (9.66%). We also reported families: Deinopidae, Hersiliidae, Nephilidae, Pisauridae, and Scytodidae that are some interesting records for the region. This is the first inventory of spider fauna from this region including several undescribed species.